Rising Stakes for Health Care-Associated Infection Prevention: Implications for the Clinical Microbiology Laboratory - Diekema, Daniel J. (Journal of clinical microbiology, 2017)
Health care-associated infection (HAI) rates are subject to public reporting and are linked to hospital reimbursement from the Centers for Medicare and Medicaid Services (CMS). The increasing pressure to lower HAI rates comes at a time when advances in the clinical microbiology laboratory (CML) provide more-precise and -sensitive tests, altering HAI detection in ways that may increase reported HAI rates. I review how changing CML practices can impact HAI rates and how the financial implications of HAI metrics may produce pressure to change diagnostic testing practices. Finally, I provide suggestions for how to respond to this rapidly changing environment.